Digital Literacy Skills Against Children's Personal Data Protection on Social Media - Likha Sari Anggreni; Nunung Prajarto; Novi Kurnia (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
The popularity of social media attracts many people to participate in various activities every day. Social media usually comes in the form of  audio, graphics, video text and animations that provide convenience to its users to  disseminate and access  information quickly amd easily. Without realizing it, parents often show off their children's personal data in their parents' and children's accounts, usually for personal or business purposes. The purpose of this study is to examine more about the efforts made by parents to protect children's data privacy on Instagram social media accounts. This study uses  the meta-analysis method of the literature study on previous studies. In this study, we want to see how the role of digital literacy in protecting children's personal data is and   how to conceptualize children's self-protection digital literacy on social media. The findings of this study  with the concept, threats, recommendations regarding the importance of digital literacy for personal data protection and conceptual integration can be used as a reference in  further research. The protection of children's personal data is important  to thwart  the threat of  cyber crime, violence and online extortion. It can also be one of the guarantees for children’s good growth and development because the data will   not be misused by other parties for financial gain or  to threaten children.